Перспективи податкового стимулювання НДДКР в Україні: досвід інноваційно розвинутих країн - Мазур, Ю.О. (Економіка промисловості, 2016)
Статтю присвячено виявленню напрямів податкового стимулювання НДДКР в Україні для забезпечення інноваційного розвитку економіки країни. Розглянуто зміни в законодавстві України щодо використання інструментів стимулювання НДДКР. Обґрунтовано, що всучасних умовах Податковим кодексом України не передбачено скорочення податкових зобов’язань платників податків у результаті здійснення ними інноваційної діяльності. На практиці податкове стимулювання інноваційної діяльності в Україні розкривається через звільнення від оподаткування основними бюджетоутворюючими податками законодавчо встановлених видів господарської діяльності. Визначено, що сучасна практика інноваційного розвитку країн світу передбачає значне зростання інвестицій у НДДКР. Одним із найбільш гнучких інструментів державної політики у сфері інновацій виступають податкові стимули НДДКР. Запропоновано впровадження механізму надання інвестиційного податкового кредиту у сфері НДДКР у вигляді знижки на податок на прибуток підприємств, єдиний податок та податок на доходи фізичних осіб для інноваційно активних суб’єктів господарювання. Обґрунтовано, що впровадження запропонова- них напрямів стимулювання НДДКР (за умови стабільного інституційного середовища і незмінних протягом багатьох років правил податкового стимулювання НДДКР) сприятиме поступовому переходу до інноваційного розвитку економіки країни, формуванню нового, більш ефективного механізму державно-приватного партнерства у науково-технічній сфері та в цілому більш сприятливого інституційного середовища господарювання. Статья посвящена выявлению направлений налогового стимулирования НИОКР в Украине для обеспечения инновационного развития экономики страны. Рассмотрены изменения в законодательстве Украины относительно использования инструментов стимулирования НИОКР. Обосновано, что в современных условиях Налоговым кодексом Украины не предусмотрено сокращение налоговых обязательств плательщиков налогов в результате осуществления ими инновационной деятельности. На практике налоговое стимулирование инновационной деятельности в Украине раскрывается через освобождение от налогообложения основными налогами законодательно установленных видов хозяйственной деятельности. Определено, что современная практика инновационного развития во многих странах мира предусматривает значительный рост инвестиций в НИОКР. Одним из наиболее гибких инструментов государственной политики в сфере инноваций выступают налоговые стимулы НИОКР. Предложено внедрение механизма предоставления для инновационно активных субъектов хозяйствования инвестиционного налогового кредита в виде скидки на налог на прибыль предприятий, единый налог и налог надоходы физических лиц, занятых в сфере НИОКР. Обосновано, что внедрение предложенных направлений стимулирования НИОКР (при условии стабильной институциональной среды и неизменных на протяжении многих лет правил налогового стимулирования НИОКР) будет способствовать постепенному переходу к инновационному развитию экономики страны, формированию нового, более эффективного механизма государственно-частного партнерства в научно-технической сфере и в целом более благоприятной институциональной среды хозяйствования. In modern conditions decreasing total GDP in comparative prices reduces the share of innovation expenditures in GDP, which indicates a lack of innovation development in Ukrainian economy. The article is devoted to identifying the prospects of research and development (RD) tax incentives in Ukraine for the economy innovation development. The changes in the Ukrainian legislation in the sphere of the RD stimulation are reviewed. It is proved that in modern conditions the Tax Code of Ukraine does not provide a reduction of tax liabilities as a result of private innovation activities. In practice, the tax incentives for innovative activity in Ukraine are revealed through tax exemption of priority economic activities from basic taxes, such as income tax of enterprises and VAT. One of the most flexible instruments of state policy in the field of innovation is the RD tax incentives. RD tax incentives are used throughout the world to encourage RD in private sector. It was determined that the current practice of innovation development in many countries provides a significant increase in investment in RD. Tax credits and other fiscal incentives (for example, tax allowances) increase investments in RD activity. Governments use tax credits both as a tool to support broad RDand a targeted public policy to foster innovation in specific fields such as small and medium enterprises, energy, information systems, and others. The main requirement of RD investment tax incentives should be the systematic innovation activity in the sphere of the scientific and technological progress in terms of scientific or technological uncertainty. The study compares the design features and generosity of RD tax incentives across innovation developed countries. In general, the choice of RD tax measures depends on country-level variables such as overall innovation performance and the nature of corporate tax systems. Gradual implementation of the mechanism of investment tax credit in the form of allowances for innovation economic entities is offered. RD investment tax credit should be given to enterprises that operate in Ukraine. It may be granted for income tax of enterprises, personal income tax and a flat tax. The reduction is made for each tax, which provided for RD tax credit. The decision to support private RD through tax incentives is important for innovation development of Ukraine within the context of modern political and economic changes. The design of Ukrainian RD tax incentives depends on the general configuration of the tax system and the particular policy goals being pursued.